Theo Conover: capstone - Conover, Theo, artist (Colorado State University. Libraries, 2024)
The artist's statement: Good design uses visual elements to convey deeper meanings that may always not be noticed consciously, but feels comfortable at a subconscious level; more simply, good design is invisible and feels seamless. My name is Theo Conover! I am a graphic designer who is passionate about combining the logical aspect of marketing with the artistic side of visual art. In my free time, I love hiking with my dog, rock climbing, and building computers! In my designs, I strive to create pieces that feel visually intuitive and seamless while being creative enough to stand out at the same time. I try to use a combination of digital and analog tools when drafting or creating final pieces, since relying entirely on digital means can sometimes make everything look or feel the same. In my designs, I make sure to pay close attention to typography, hierarchy of information, and composition in order to guide the viewer through the design. Clean, conceptual, and creative are different words that could describe my overall style. In terms of growth as an artist, I feel inspired to push my own typography by people like Jessica Hische and Louise Fili, who are able to hand-letter their own type in very creative ways.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design